Short article: Influence of regulatory NLRC5 variants on colorectal cancer survival and 5-fluorouracil-based chemotherapy - Catalano, Calogerina; da Silva Filho, Miguel I; Jiraskova, Katerina; Vymetalkova, Veronika; Levy, Miroslav; Liska, Vaclav; Vycital, Ondrej; Naccarati, Alessio; Vodickova, Ludmila; Hemminki, Kari; Vodicka, Pavel; Weber, Alexander N R; et al. (European journal of gastroenterology & hepatology, 2018)
BACKGROUND: NLRC5 is an interferon γ-inducible protein, which plays a role in immune surveillance with a potential influence on cancer survival. OBJECTIVE: We aimed to evaluate the effect of potential regulatory variants in NLRC5 on overall survival and survival after 5-fluorouracil (5-FU)-based therapy of colorectal cancer (CRC) patients. PATIENTS AND METHODS: We carried out a case-only study in a Czech population of 589 cases; 232 received 5-FU-based therapy. Eleven variants within NLRC5 were selected using in-silico tools. Associations between polymorphisms and survival were assessed by Cox regression analysis adjusting for age at diagnosis, sex, and TNM stage. Survival curves were derived using the Kaplan-Meier method. RESULTS: Two variants showed a significant association with survival. All patients and metastasis-free patients at the time of diagnosis (pM0) who were homozygous carriers of the minor allele of rs27194 had a decreased overall survival (OSall and OSpM0) and event-free survival (EFSpM0) under a recessive model (OSall P=0.003, OSpM0 P=0.005, EFSpM0 P=0.01, respectively). OS was also decreased for all patients and for pM0 patients who carried at least one minor allele of rs289747 (OSall P=0.03 and OSpM0 P=0.003, respectively). Among CRC patients, who underwent a 5-FU-based adjuvant regimen, rs12445252 was associated with OSall, OSpM0 and EFSpM0, according to the dosage of the minor allele T (OSall P=0.0004, OSpM0 P=0.0001, EFSpM0 P=0.008, respectively). CONCLUSION: Our results showed that polymorphisms in NLRC5 may be used as prognostic markers of survival of CRC patients, as well as for survival in response to 5-FU treatment.
Keywords: Polymorphism, Single Nucleotide; proporcionální rizikové modely; Humans; Case-Control Studies; fluoruracil; genetické asociační studie; lidé středního věku; Proportional Hazards Models; studie případů a kontrol; Biomarkers, Tumor; intracelulární signální peptidy a proteiny; jednonukleotidový polymorfismus; Female; rizikové faktory; Aged; dospělí; protokoly protinádorové kombinované chemoterapie; frekvence genu; Phenotype; výsledek terapie; senioři; lidé; přežití bez známek nemoci; časové faktory; nádorové biomarkery; Adult; Intracellular Signaling Peptides and Proteins; staging nádorů; ženské pohlaví; Kaplanův-Meierův odhad; kolorektální nádory; Genetic Association Studies; Male; Middle Aged; fenotyp; Genetic Predisposition to Disease; genetická predispozice k nemoci; Antineoplastic Combined Chemotherapy Protocols; Treatment Outcome; Czech Republic; Aged, 80 and over; Fluorouracil; Gene Frequency; Disease-Free Survival; senioři nad 80 let; Kaplan-Meier Estimate; Neoplasm Staging; Česká republika; mužské pohlaví; Time Factors; Colorectal Neoplasms; Risk Factors